Karakteristik Jenis Kemasan terhadap Mutu Kentang (Solanum tuberosum L.) Konsumsi selama Penyimpanan Suhu Dingin - Ningsih, Pipit Safitri; Pudja, Ida Ayu Rina Pratiwi; Sumiyati , Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
This study aims to find whether the use of different types of packaging can affect the quality of potatoes and to find out which types of packaging produce good-quality potatoes during cold storage. This study used a completely randomized design with one treatment factor, namely two different types of packaging. Parameters observed were weight loss, texture, sugar content, color, cooling rate, freshness level, and material damage. The results showed that polypropylene packaging was the best with a parameter value of weight loss of 0.05%, texture 65,7d, sugar content of 8.50 Brix, color (L 35.56, a 19.33, b 26.76), freshness level of 10.50℃ during cold storage. The effect of polypropylene plastic packaging can maintain the freshness of potatoes until the 56th day compared to potatoes packaged with polyethylene plastic.